Partisipasi Mahasiswa dalam Mempromosikan Jurusan Bimbingan dan Konseling Islam Untuk Meningkatkan Minat Studi di Jurusan Bimbingan dan Konseling Islam IAIN Lhokseumawe - Muhammad Syauki; Desy Murni Lasari; Rizqi Wahyudi (Medan State University, 2023)
The objectives of this research are: To find out the participation of BKI students in increasing the interest in studying prospective students at the Islamic Guidance and Counseling Department of IAIN Lhokseumawe. In order to know the obstacles and challenges of students in promoting the Islamic Guidance and Counseling Department of IAIN Lhokseumawe. The method in this study is to use a type of descriptive method with a qualitative approach, data collection methods using observation, interviews and documentation. The results of this study are: first, the participation of Islamic guidance and counseling students in increasing the interest in studying prospective students at the Islamic Guidance and Counseling Department of IAIN Lhokseumawe, that student participation in increasing interest in study can be called active participation, active participation carried out by students in the form of participation in the implementation of explaining the majors to family, high school friends and the community in the neighborhood where they live. As well as social participation, which is meant by socializing, making video profiles of majors and activities, in this case, students work together in the success of the activity. Second, the obstacles and challenges of students in promoting the Islamic Guidance and Counseling Department of IAIN Lhokseumawe, namely: students experience barriers to lack of student capability about majors so that promotional communication when explaining is hampered or ineffective, obstacles are lack of support from the academic community for the promotion ambassador program for majors and in This research finds the challenges of students in explaining the BKI major to people who have difficulty understanding this major.